Hypoplasia of the posterior mitral valve leaflet and bicuspid aortic valve. A very rare combination to find in an adult patient (2019)
The congenital heart diseases are a diagnostic challenge for the clinician, particularly when they are presented in an adult. These types of anomalies that are observed in the mitral valve can be presented in isolated form or together with other heart defects. The case is presented of a patient with severe hypoplasia of the posterior mitral valve leaflet. This anomaly is, under normal conditions, fatal before birth or very symptomatic during childhood, and its delayed presentation is extremely rare and difficult to find in the adult. This the first case reported, not only in this country, but in the whole of South America. © 2018 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular